Bioavailability of pelargonidin-3-O-glucoside and its metabolites in humans following the ingestion of strawberries with and without cream - Mullen, W.; Edwards, Christine; Serafini, M.; Crozier, A. (2008)
Plasma and urine were collected over a 24 h period after the consumption by humans of 200 g of strawberries, containing 222 µmol of pelargonidin-3-O- glucoside, with and without cream. The main metabolite, a pelargonidin-O- glucuronide, reached a peak plasma concentration (C max) of 274 ± 24 nmol/L after 1.1 ± 0.4 h (t max) when only strawberries were ingested. When the strawberries were eaten with cream, the C max was not statistically different but the t max at 2.4 ± 0.5 h was delayed significantly (p < 0.001). The pelargonidin-O-glucuronide, along with smaller quantities of other metabolites, was also excreted in urine in quantities corresponding to ca. 1% of anthocyanin intake. The quantities excreted over the 0 - 24 h collection period were not influenced significantly by cream. However, the 0 - 2 h excretion of anthocyanin metabolites was significantly lower when the strawberries were eaten with cream, whereas the reverse occurred during with the 5 - 8 h excretion period. In keeping with these observations, measurement of plasma paracetamol and breath hydrogen revealed that cream delayed gastric emptying and extended mouth to cecum transit time. © 2008 American Chemical Society.